2013
DOI: 10.2119/molmed.2013.00011
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Studies in the mdx Mouse Model of Duchenne Muscular Dystrophy with the Histone Deacetylase Inhibitor Givinostat

Abstract: Previous work has established the existence of dystrophin-nitric oxide (NO) signaling to histone deacetylases (HDACs) that is deregulated in dystrophic muscles. As such, pharmacological interventions that target HDACs (that is, HDAC inhibitors) are of potential therapeutic interest for the treatment of muscular dystrophies. In this study, we explored the effectiveness of long-term treatment with different doses of the HDAC inhibitor givinostat in mdx mice-the mouse model of Duchenne muscular dystrophy (DMD). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
102
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(110 citation statements)
references
References 24 publications
6
102
1
1
Order By: Relevance
“…In fact, pharmacological inhibitors of HDACs have also shown promise in preclinical models of diseases of muscle, including amyotrophic lateral sclerosis (Yoo & Ko, 2011), spinal muscular atrophy (Minamiyama et al ., 2004) and muscular dystrophy (Consalvi et al ., 2013). For example, HDAC inhibitors reduce fibrosis and improve muscle function in a mouse model of muscular dystrophy (Consalvi et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, pharmacological inhibitors of HDACs have also shown promise in preclinical models of diseases of muscle, including amyotrophic lateral sclerosis (Yoo & Ko, 2011), spinal muscular atrophy (Minamiyama et al ., 2004) and muscular dystrophy (Consalvi et al ., 2013). For example, HDAC inhibitors reduce fibrosis and improve muscle function in a mouse model of muscular dystrophy (Consalvi et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, HDAC inhibitors reduce fibrosis and improve muscle function in a mouse model of muscular dystrophy (Consalvi et al ., 2013). Because pharmacological inhibitors of class I and II HDACs have been shown to ameliorate neuromuscular disease in animal models, we asked whether the general HDAC inhibitor butyrate could attenuate muscle atrophy and improve metabolism during aging.…”
Section: Introductionmentioning
confidence: 99%
“…In amyotrophic lateral sclerosis, HDAC inhibitors have been proposed as potential drugs to ameliorate patient symptoms [104,105] . In the case of muscular dystrophy, HDAC inhibitors have been extensively studied using the mdx mouse model [106] ; currently, these drugs are under review in a clinical trial for muscular dystrophy [107] . Their effects are believed to be primarily due to the inhibition of class Ⅰ HDACs [108] .…”
Section: Resultsmentioning
confidence: 99%
“…[10,11] In principle, the rationale for the use of HDACi in the treatment of DMD was provided by the finding that dystrophin-deficient muscles display an aberrant, constitutive activation of HDAC2, as a consequence of reduced nitric oxide (NO)-mediated NO-dependent S-nitrosylation in myofibers. [12] Moreover, recent studies have revealed complex epigenetic networks targeted by HDACi in MuSCs and FAPs.…”
Section: Hdac Inhibitors For Muscular Dystrophies: Progress and Prospmentioning
confidence: 99%
“…Studies with HDACi in mdx mice demonstrated that the morphological recovery is accompanied by increased muscle strength and exercise performance. [10,11] Thus, matching functional tests, such as 6 Minute Walk Test (6MWT) and North Star Ambulatory Assessment, with the histological evaluation of treated muscles, will be mandatory to reveal the efficacy of HDACi and other pharmacological interventions in DMD patients.…”
Section: Expert Opinionmentioning
confidence: 99%